Mobilization with movement, thoracic spine manipulation, and dry needling for the management of temporomadibular disorder: A prospective case series - Gonzalez-Iglesias, Javier; Cleland, Joshua; Neto, Francisco; Hall, Toby; Fernandez-de-las-Penas, Cesar (Taylor and Francis, 2013)
The purpose of this case series was to describe the outcomes of patients with temporomandibular disorder (TMD) treated with mobilization with movement (MWM) directed at the temporomandibular joint (TMJ) and the cervical spine, thoracic manipulation, and trigger point (TrP) dry needling. Fifteen patients with TMD completed the Steigerwald/Maher TMD disability questionnaire, the Visual Analog Scale (VAS), and maximal mouth opening (MMO) at baseline. The VAS and MMO were also collected at 15 days posttreatment and at a 2-month follow-up, and the Steigerwald/Maher TMD disability questionnaire was completed at the 2-month follow-up. Repeated measure ANOVAs were used to determine the effects of the intervention on each outcome. Within-group effect sizes were calculated in order to assess clinical effectiveness. Fifteen patients participated in this case series. The ANOVA revealed significant decreases (all, p < 0.01) VAS mean, VAS Worst, and VAS Best between baseline and final visit of 25.7 (95% CI; 17.7, 33.8); 33.2 (95% CI; 23.4, 43.0); 18.4 (12.1, 24.7); and 28.3 (95% CI; 18.8, 37.9); 36.1 (95% CI; 25.0, 47.3); 19.7 (95% CI; 12.8, 26.7) between baseline and the 2-month follow-up periods, respectively. Additionally, the ANOVA revealed significant increases (all, < 0.01) in MMO and disability following the physical therapy management strategy between baseline and final visit with a mean of 11.4 (95% CI, 6.9, 15.9) and 10.2 (95% CI, 5.2, 15.2) between baseline and the 2-month follow-up. Within-group effect sizes were large (d > 1.0) for all outcomes at both follow-up periods. Patients with TMD treated with a multimodal treatment exhibited significant and clinical improvements in pain intensity, disability, and MMO.